2018
DOI: 10.1016/j.cstp.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of demand management policy in reducing traffic congestion and environmental pollution: Car-free day and odd-even plate measures for Bandung city in Indonesia

Abstract: Traffic congestion has been a major problem in big cities around the world, not to mention several large cities in Indonesia. Bandung is the second largest metropolitan area after Jakarta in Indonesia which suffers from extreme levels of congestion. With a high number of motorcycles and large private car population, congestion in this city is ever growing worsening the environment. While the local authorities struggle to find resources to fund capital intensive capacity expansion projects, this research explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…This study employs the 4-step network modeling approach as explained in [9] to analyze road network performance in the southern area of West Java, without and with road widening. Inputs that are required are i) the road network data and ii) the origin-destination matrix (O-D matrix).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study employs the 4-step network modeling approach as explained in [9] to analyze road network performance in the southern area of West Java, without and with road widening. Inputs that are required are i) the road network data and ii) the origin-destination matrix (O-D matrix).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have carried out analyses related to mobility to make an area or cities more accessible. For instance, [9] carried out a study on traffic management policy, namely odd-even plate number and car-free day policy. The study identified the impact of the policies on road network volume capacity ratio, which influences traffic speed, and hence accessibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Indonesia, traditional markets play a key role in supply chains, with trade accounting for more than 80% of the total trade volume (Dyck et al 2012). In Fig.…”
Section: Independent Retailers and Traditional Markets In Bandungmentioning
confidence: 99%
“…This study set the effectiveness rate between 0 to 40 percent, showing the same result from the previous solution; the higher successful implementation rate will result in the lowest carbon emission. However, this is inversely proportional to another study that mentioned that an odd-even policy is applicable for the short term period only [30] because it motivates the drivers to look for alternative routes to avoid its implementation. In addition, it is also shifting the habit of driving at certain hours.…”
Section: Odd-even Policymentioning
confidence: 99%